Anisotropic Iridescence and Polarization Patterns in a Direct Ink Written Chiral Photonic Polymer (Adv. Mater. 39/2021). Issue 39 (1st October 2021) - Sol, Jeroen A. H. P.; Sentjens, Henk; Yang, Lanti; Grossiord, Nadia; Schenning, Albertus P. H. J.; Debije, Michael G.
Abstract : Chiral Photonic Polymers In article number 2103309, Albertus P. H. J. Schenning, Michael G. Debije, and co‐workers show that using direct ink writing, unconventional chiral nematic objects can be generated, which show a bright iridescent color from normal incidence, or only from sharp angles of observation depending on the writing speed. The cover is a polarized optical microscopy image showing a detail from the free‐standing Morpho‐inspired print.